2021
DOI: 10.1007/s11663-021-02059-z
|View full text |Cite
|
Sign up to set email alerts
|

Precious Metal Distributions Between Copper Matte and Slag at High $$ P_{{{\text{SO}}_{ 2} }} $$ in WEEE Reprocessing

Abstract: The distributions of precious metals (gold, silver, platinum, and palladium) between copper matte and silica-saturated FeOx-SiO2/FeOx-SiO2-Al2O3/FeOx-SiO2-Al2O3-CaO slags were investigated at 1300 °C and $$ P_{{{\text{SO}}_{ 2} }} $$ P SO 2 = 0.5 atm. The experiments were carried out in silica crucibles under flowing CO-CO2-SO2-Ar gas atmosphere. The concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The laser spot size was selected as 65 µm for the air-atmosphere experiments, and 40 µm for the argon-atmosphere samples, due to the limited size of slag areas available. The obtained detection limits of EPMA and LA-ICP-MS are shown in Table 3, and more detailed information about the technique adopted in our study can be found in the references [34,40,[42][43][44].…”
Section: Analysesmentioning
confidence: 99%
“…The laser spot size was selected as 65 µm for the air-atmosphere experiments, and 40 µm for the argon-atmosphere samples, due to the limited size of slag areas available. The obtained detection limits of EPMA and LA-ICP-MS are shown in Table 3, and more detailed information about the technique adopted in our study can be found in the references [34,40,[42][43][44].…”
Section: Analysesmentioning
confidence: 99%
“…To address this issue, the technique of gold collection in matte is proposed and applied in gold smelting industries due to its significant advantages, such as large processing scale, low cost, and strong raw-material adaptability. This technique not only enhances the recovery rate of valuable metals, including gold, silver, and copper but also facilitates the comprehensive recovery of rare and precious metals [8,9]. As is known, copper can serve as an effective collector of gold.…”
Section: Introductionmentioning
confidence: 99%
“…This approach utilizes high-temperature thermal processes to extract and separate metals from electronic waste, providing an efficient and reliable means of metal recovery [19,20]. Valuable metals such as copper (Cu), gold (Au), silver (Ag), palladium (Pd), and platinum (Pt) can be successfully recovered from complex electronic waste streams using pyrometallurgical techniques [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%